Mendorong Sustainability Performance UMKM Kerajinan Logam Di Provinsi Bali: Sinergi Material Flow Cost Accounting Dan Waste Management - Komang Tri Yasrawan; Kadek Mitananda Pradnya Nugraha; I Gusti Made Priyambhada Putra; Komang Dandy Andriadi; Theresia Dirda Rosari Widyadara; Gd.Pandya Wicaksana Gara (Universitas Pendidikan Ganesha, 2026)
This study aims to examine the effect of Material Flow Cost Accounting (MFCA) on sustainability performance through waste management. The population of this study consisted of metal craft MSMEs in Bali Province. The sample size was determined based on a G*Power calculation with a 5% significance level, 95% statistical power, an effect size of 0.15, and two predictors, resulting in a minimum required sample of 107 respondents. To enhance the accuracy and reliability of the analysis, a larger sample of 130 respondents was utilized. Data were collected using questionnaires and analyzed employing the Partial Least Squares Structural Equation Modeling method via SmartPLS version 4 software. The findings indicate that MFCA has a positive effect on waste management; both MFCA and waste management positively affect sustainability performance; and waste management mediates the positive effect of MFCA on the sustainability performance of metal craft MSMEs in Bali Province. Keywords: material flow cost accounting, sustainability performance, waste management